Teaching about Asian Pacific Americans: Effective Activities, Strategies, and Assignments for Classrooms and Communities - Chen, Edith Wen-Chu; Omatsu, Glenn (Rowman & Littlefield Publishers, 2006)
The number of Asian American students in schools and colleges has soared in the last twenty-five years, and they make up one of the fastest growing segments of the student population. However, classroom material often does not include their version of the American experience. Teaching about Asian Pacific Americans was created to address this void. This resource guide provides interactive activities, assignments, and strategies for classrooms or workshops. Those new to the field of Asian American studies will appreciate the background information on issues that concern Asian Pacific Americans, while experts in the field will find powerful, innovative teaching activities that clearly convey established and new ideas. The activities in this book have been used effectively in classrooms, workshops for staff and practitioners in student services programs, community-based organizations, teacher training programs, social service agencies, and diversity training. Teaching About Asian Pacific Americans serves as a critical resource for anyone interested in race, ethnicity, and Asian Pacific American communities.